Phylogeny, Ecology, and Heart Position in Snakes - Gartner, Gabriel E. A.; Hicks, James W.; Manzani, Paulo R. [UNESP]; Andrade, Denis V. [UNESP]; Abe, Augusto Shinya [UNESP]; Wang, Tobias; Secor, Stephen M.; Garland, Theodore (Univ Chicago Press, 2010)
The cardiovascular system of all animals is affected by gravitational pressure gradients, the intensity of which varies according to organismic features, behavior, and habitat occupied. A previous nonphylogenetic analysis of heart position in snakes-which often assume vertical postures-found the heart located 15%-25% of total body length from the head in terrestrial and arboreal species but 25%-45% in aquatic species. It was hypothesized that a more anterior heart in arboreal species served to reduce the hydrostatic blood pressure when these animals adopt vertical postures during climbing, whereas an anterior heart position would not be needed in aquatic habitats, where the effects of gravity are less pronounced. We analyzed a new data set of 155 species from five major families of Alethinophidia (one of the two major branches of snakes, the other being blind snakes, Scolecophidia) using both conventional and phylogenetically based statistical methods. General linear models regressing log 10 snout-heart position on log 10 snout-vent length (SVL), as well as dummy variables coding for habitat and/or clade, were compared using likelihood ratio tests and the Akaike Information Criterion. Heart distance to the tip of the snout scaled isometrically with SVL. In all instances, phylogenetic models that incorporated transformation of the branch lengths under an Ornstein-Uhlenbeck model of evolution (to mimic stabilizing selection) better fit the data as compared with their nonphylogenetic counterparts. The best-fit model predicting snake heart position included aspects of both habitat and clade and indicated that arboreal snakes in our study tend to have hearts placed more posteriorly, opposite the trend identified in previous studies. Phylogenetic signal in relative heart position was apparent both within and among clades. Our results suggest that overcoming gravitational pressure gradients in snakes most likely involves the combined action of several cardiovascular and behavioral adaptations in addition to alterations in relative heart location.